Telaah Politik Hukum terhadap Delik Keagamaan dalam KUHP Baru - Abdillah Halim (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
Religious offenses originate from material in Law no. 1/PNPS/1965 concerning Prevention of Abuse and/or Blasphemy of Religion. Material in Law no. 1/PNPS/1965 has repeatedly requested a judicial review of the Constitutional Court, with various arguments of damage to the constitutional rights of the applicants, but the Constitutional Court passed Decision Number 140/PUU-VII/2009, Decision Number 84/PUU-X/2012, Decision Number 56/ PUU-XV/2017, Decision Number 76/PUU-XVI/2018, and finally Decision Number 5/PUU-XVII/2019, essentially rejected the application. In the new Criminal Code, religious offenses are maintained with several new formulations. This article examines the political aspects of religious offense law in the new Criminal Code, especially in relation to the ideal legal ideals to be achieved through the accommodation and implementation of religious offenses in the Indonesian context. This study yielded several important points, first, religious offenses were once used by the colonial government to control the potential resistance of tarekat and Ratu Adil groups, so from this it can be understood that the political interests of the ruling regime were a determining factor in the interpretation and implementation of religious offenses. Second, the aim of religious offense law in the new Criminal Code is aimed at protecting freedom of religion and belief even for religious groups, so that the formulation of the offense also avoids word choices that allow excessive use which has the potential to criminalize religious groups and beliefs outside of orthodoxy. Third, a productive space for interpretation among law enforcers regarding religious offenses must be maintained and guidelines for the implementation of religious offenses for them must be immediately prepared, an interpretation space and guidelines that are compatible with the principles of guaranteeing substantive equality and upholding distributive justice, especially for religious groups and beliefs outside of orthodoxy. mainstream.